Degree of concordance of Clostridioides difficile strains in adults with community-associated C. difficile infection and infants with C. difficile colonization. (19th June 2021) - Clayton, Jason A.; Cadnum, Jennifer L.; Senders, Shelly; Jinadatha, Chetan; Chatterjee, Piyali; Choi, Hosoon; Allton, Yonhui; Donskey, Curtis J.; Toltzis, Philip
Abstract: Background: Infants asymptomatically excrete Clostridioides difficile during their first year of life, suggesting that they may represent a source of infection for adults who acquire community-associated C. difficile infection (CA-CDI). The genetic relationship of C. difficile strains from asymptomatic infants and adults with CA-CDI is not well defined. Methods: In this study, 50 infants were recruited at birth, and stool samples were collected at routine well-child visits. Adult stool samples collected during the same period and geographical area from patients who were diagnosed with CA-CDI were selected for comparison. C. difficile was cultivated and probed by PCR for toxin genes and were typed by PCR fluorescent ribotyping. Isolates from adults and infants with shared ribotypes were subjected to whole-genome sequencing (WGS). Results: Of these 50 infants, 36 were positive for C. difficile at least once in their first year of life, with a peak incidence at 6 months. Among 180 infant stool samples, 48 were positive. Of 48 isolates from positive stools, 29 were toxigenic by polymerase chain reaction (PCR) and 8 of 48 stool samples were positive for toxin by enzyme immunoassays (EIAs). Ribotypes F106 and F014-020 were present in both colonized infants and adults with CA-CDI. WGS identified 1 adult–infant pair that differed by 5 single-nucleotide polymorphisms (SNPs). Also, 4 additional adult–infant clusters differed by ≤16 SNPs. Conclusions: Infants that are colonized with C. difficile share ribotypes with adults from the same geographical region with CA-CDI. Selected isolates in the 2 populations show a genetic relationship by WGS.